PREDIKSI JUMLAH PENYAKIT INFEKSI SALURAN PERNAPASAN AKUT (ISPA) MENGGUNAKAN SIMPLE MOVING AVERAGE - Priyono, Agus; Shodiq, Muhammad; Ramanda, Febri (Jurnal Informatika Medis, 2023)
Health problems in Indonesia are still a topic that really needs to be developed and researched considering that disease problems in Indonesia are diverse and contribute to high death rates. Acute Respiratory Infection (ARI) is a disease that often occurs in society and is considered normal or not dangerous, but can cause death. A group of diseases included in ISPA are, Pneumonia, Influenza, and Respiratory Syncytial Virus (RSV). ISPA disease in Indonesia contributes to the highest number of deaths, so there is a need for action or policy that can control ISPA disease in the future. The aim of this research is to apply the simple moving average method to predict ARI disease. This method is simple in prediction but has optimal results in some use cases. This research uses annual data from 2007 to 2022 for the calculation method. The research results show that the simple moving average method provides accurate prediction results with a MAPE value of 11% for predicting the number of ISPA cases. It is hoped that the results of this research can determine policies for controlling ARI diseases Keywords: Acute Respiratory Infection, Prediction, Simple Moving Average